Les langues officielles au Canada - Brun, Henri; Tremblay, Guy (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
This article is a summary of the law governing official languages in Canada. The paper also concentrates on present controversial issues raised by judicial pronouncements on the Official Languages Act and on section 133 of the B.N.A  Act. The first section studies the « constitutional » aspect of the question of official languages in Canada, as to whether the relevant provisions are considered to be entrenched or not. Special emphasis is placed on the scope and effect of section 133 as interpreted so far. Federal and provincial legislative powers with respect to languages are then discussed, as well as the inapplicability of section 93 of the B.N.A. Act. Finally, the main constitutional proposals relating to linguistic rights are outlined. The next two sections deal with federal and provincial legislation and their judicial application. At the federal level, the Official Languages Act and its apparent weaknesses attract particular attention. At the provincial level, a survey is taken of Quebec's successive Acts respecting languages, and « Bill 101 » is especially considered in relation to the Charter of human rights and freedoms. The conclusion is that the unsatisfactory state of the law of official languages in Canada may well drag on if general agreement is not reached on a renewed federation.